Efektivitas Fungsi Koordinasi Dinas Satuan Polisi Pamong Praja dan Pemadam Kebakaran dengan Camat Di Kabupaten Sinjai dalam Penegakan Peraturan Daerah Nomor 4 Tahun 2015 - Mulawangsa M; Adi Nawir; Sapriadi Sapriadi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2021)
This paper aims to find out the Coordination Function of the Civil Service Police Unit and firefighters with the Camat in Sinjai Regency in the Enforcement of Regional Regulation Number 4 of 2015. The type of research is qualitative. The results of the study indicate that the effectiveness in enforcing the Regional Regulation through two coordination methods, First, Horizontal Coordination is quite effective, optimizing the Coordination Function of the Civil Service Police Unit and Firefighters with the Camat in Sinjai Regency. Second, Vertical Coordination shows quite effective results. This is because the cooperation between officials even though they are at different hierarchical levels in the organizational structure can be responsible for the peace and order of society.